2022
DOI: 10.1212/wnl.0000000000201113
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing Hormone Therapy Over Vigabatrin as the First Treatment for Infantile Spasms

Abstract: Background and Objectives:Infantile spasms (IS) are early childhood seizures with potentially devastating consequences. Standard therapies (adrenocorticotropic hormone [ACTH], high-dose prednisolone, and vigabatrin) are strongly recommended as the first treatment for IS. While this recommendation comes without preference for one standard therapy over another, early remission rates are higher with hormone therapy (ACTH and high-dose prednisolone) when compared to vigabatrin. Using quality improvement (QI) metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Another quality improvement study of sequential therapy (prioritizing initial hormonal therapy over vigabatrin followed by routine initiation of a second treatment after 14 days from the failed first treatment) ultimately resulted in a remission rate of 75.9% within 3 months. 7 In the future, early sequential therapy may become another reasonable treatment option for combination therapy for clinicians. A recent study evaluating the treatment response to initial standard therapy (ACTH, prednisolone, or vigabatrin) showed that remission can be identified as early as treatment day 7 in nearly 80% of responders.…”
Section: Medical Indications: First Quadrantmentioning
confidence: 99%
See 1 more Smart Citation
“…Another quality improvement study of sequential therapy (prioritizing initial hormonal therapy over vigabatrin followed by routine initiation of a second treatment after 14 days from the failed first treatment) ultimately resulted in a remission rate of 75.9% within 3 months. 7 In the future, early sequential therapy may become another reasonable treatment option for combination therapy for clinicians. A recent study evaluating the treatment response to initial standard therapy (ACTH, prednisolone, or vigabatrin) showed that remission can be identified as early as treatment day 7 in nearly 80% of responders.…”
Section: Medical Indications: First Quadrantmentioning
confidence: 99%
“…Another quality improvement study of sequential therapy (prioritizing initial hormonal therapy over vigabatrin followed by routine initiation of a second treatment after 14 days from the failed first treatment) ultimately resulted in a remission rate of 75.9% within 3 months. 7 …”
Section: Body Of Reviewmentioning
confidence: 99%